A Study on Growth and Prospect of Digital India Campaign: Examining the Implications and Prospects of Digital India Campaign (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Digital India power is a dream venture of the Indian Government which turned into released on 1 July 2015 through Prime Minister Narendra Modi to rework India into an informed economic system and digitally empowered society, alongside exact governance for residents with a goal of presenting participative, obvious and responsive authorities. Digital India imagines, commonplace virtual literacy and approachability for all virtual assets for residents through making sure that the assets and offerings are accessible in local languages and presenting virtual scaffold to participatory governance making sure convenience, like making all authorities certificate and files to be had at the Cloud with portability. The goal of this paper is to realize the effect, demanding situations of virtual India on all factors of governance and development with inside the high-satisfactory of existence of residents. The studies method is descriptive cum analytical in nature and the statistics for this examine is accrued thru secondary reasserts together with websites, studies journals, newspapers, magazines etc. The examine offers a positive notion of presenting extra employment potentialities for the young people with the intention to improve the country’s economic system if it comes into reality.